2009
DOI: 10.1161/hypertensionaha.109.140087
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Silencing of Nox2 and Nox4 Reveals Differential Roles of These NADPH Oxidase Homologues in the Vasopressor and Dipsogenic Effects of Brain Angiotensin II

Abstract: Abstract-The renin-angiotensin system exerts a tremendous influence over fluid balance and arterial pressure. Angiotensin II (Ang-II), the effector peptide of the renin-angiotensin system, acts in the central nervous system to regulate neurohumoral outflow and thirst. Dysregulation of Ang-II signaling in the central nervous system is implicated in cardiovascular diseases; however, the mechanisms remain poorly understood. Key Words: hypertension Ⅲ blood pressure Ⅲ water intake Ⅲ subfornical organ Ⅲ adenovirus Ⅲ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 51 publications
3
101
0
1
Order By: Relevance
“…Importantly, and relevant to the present findings, Ang II's actions on PVN neurons play a key role in regulating sympathetic nervous system activity in relation to cardiovascular function, particularly hypertension (8,48). Some mechanisms for these actions include elevations of inflammation and oxidant stress locally within the brain (8,33,63,74), which have also been implicated in the central regulation of energy balance (18,34). In fact, the effects of icv Ang II on energy balance are strikingly similar to those of the cytokine TNF␣ (3,18).…”
Section: Discussionsupporting
confidence: 55%
“…Importantly, and relevant to the present findings, Ang II's actions on PVN neurons play a key role in regulating sympathetic nervous system activity in relation to cardiovascular function, particularly hypertension (8,48). Some mechanisms for these actions include elevations of inflammation and oxidant stress locally within the brain (8,33,63,74), which have also been implicated in the central regulation of energy balance (18,34). In fact, the effects of icv Ang II on energy balance are strikingly similar to those of the cytokine TNF␣ (3,18).…”
Section: Discussionsupporting
confidence: 55%
“…The pressor response to central Ang II is predominently mediated by AT 1 receptor stimulation, and drinking response and release of vasopressin are mediated by both AT 1 and AT 2 receptors stimulation. 9 Peterson et al 30 showed that both nicotinamide adenine dinucleotide phosphate oxidases, NOX2 and NOX4, in the SFO contribute to Intracerebroventricular infusion of Ang II at 2.5 ng/min increases BP maximally by 20 mm Hg within the first 1 to 2 days, and BP remains at this level during the next 2 weeks. Intracerebroventricular infusion of FAD286 or eplerenone does not affect the initial increase in BP, but from day 3, reverses the elevated BP toward control values.…”
Section: Discussionmentioning
confidence: 99%
“…After screening each of the shRNAs in TIB-73 cells (an immortalized mouse hepatocyte cell line) for knockdown of G6PD protein, we selected viruses 4 and 5 (named Ad.shG6PD4 and Ad.shG6PD5) for further in vivo experiments. For knock-down of NOX4, we used a previously characterized recombinant adenoviral vector expressing shRNA against mouse NOX4 (Ad.shNOX4) (44). We used an adenovirus (Ad.shGFP) that expresses shRNA against GFP as a control (45).…”
Section: Methodsmentioning
confidence: 99%